Food and financial crises: Implications for agriculture and the poor - von Braun, Joachim (International Food Policy Research Institute, 2008)
High food prices from 2007 through mid-2008 had serious implications for food and nutrition security, macroeconomic stability, and political security. The unfolding global financial crisis and economic slowdown have now pushed food prices to lower levels. Yet the financial crunch has also decreased the availability of capital at a time when accelerated investment in agriculture is urgently needed. The food and financial crises will have strong and long-lasting effects on emerging economies and poor people. A synchronized response is needed to ease the burden on the poor and allow agriculture to face new challenges and respond to new opportunities. Three sets of complementary policy actions should be taken: (1) promote pro-poor agricultural growth, (2) reduce market volatility, and (3) expand social protection and child nutrition action. Agriculture requires strategic investment action, and the food-insecure poor need a bailout now.